2011
DOI: 10.1371/journal.pone.0028816
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Endemic Hendra Virus Infection in Flying-Foxes (Pteropus conspicillatus)—Implications for Disease Risk Management

Abstract: This study investigated the seroepidemiology of Hendra virus in a spectacled flying-fox (Pteropus conspicillatus) population in northern Australia, near the location of an equine and associated human Hendra virus infection in late 2004. The pattern of infection in the population was investigated using a serial cross-sectional serological study over a 25-month period, with blood sampled from 521 individuals over six sampling sessions. Antibody titres to the virus were determined by virus neutralisation test. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 29 publications
8
97
0
Order By: Relevance
“…Previous studies suggested that physiological stress associated with pregnancy and lactation was a risk factor for increased seroprevalence of virus infections in bats 26,27 . Similarly, a correlation between the detection of coronaviruses in female bats associated with maternity colonies has also been established 28,29 .…”
Section: Persistent or Long-term Infection Of Australian Bat Coronavirusmentioning
confidence: 98%
“…Previous studies suggested that physiological stress associated with pregnancy and lactation was a risk factor for increased seroprevalence of virus infections in bats 26,27 . Similarly, a correlation between the detection of coronaviruses in female bats associated with maternity colonies has also been established 28,29 .…”
Section: Persistent or Long-term Infection Of Australian Bat Coronavirusmentioning
confidence: 98%
“…Previous studies have suggested that a range of physiological and ecological factors constitute risk factors for Hendra virus infection in flying-foxes (Field 2005, Plowright et al 2008, Breed et al 2011, including physiological stress associated with reproduction and sub-optimal nutrition (Plowright et al 2008), and by extension pose an increased risk of spill over into another species Field et al 2012;Plowright et al 2015). Understanding Hendra virus infection dynamics in flying-foxes and the putative causal risk factors is fundamental to elaborating the disease ecology of the virus and thus effective exposure risk management in horses and humans (Figure 1.8).…”
Section: Putative Physiological Risk Factors For Hendra Virus Infectionmentioning
confidence: 99%
“…Previous studies suggest that physiological and ecological factors, including physiological stress associated with reproduction and sub-optimal nutrition constitute risk factors for infection in flyingfoxes (Field 2005;Plowright et al 2008;Breed et al 2011), and by extension pose an increased risk of spill-over into another species Field et al 2012;Plowright et al 2015). However, it is essential to know the normal range of physiological biomarkers and their possible seasonal variability before seeking physiological associations with infection and/or disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations